PERAN DAN KEDUDUKAN PEREMPUAN MANGKUNEGARAN DALAM SEJARAH PERKEMBANGAN KEBUDAYAAN JAWA MASA MANGKUNEGARA I-VIII - Dhian Lestari Hastuti; Imam Santosa; Achmad Syarief; Pribadi Widodo (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
This research focuses on the role of Mangkunegaran women in the Mangkunegaran Kadipaten, so this study focuses on women's activities in the history of the Mangkunegaran Kadipaten until Indonesia's independence. The role of women (wives) in Javanese culture cannot be separated from the perspective of the paternalistic society as konco wingking. The understanding that man (Prophet Adam) was the first human and woman was created from his left rib. Left connotes something unimportant. Although this paternalistic perspective is inherent, no research has found a relationship between the policies of the Mangkunegaran kings and women as konco wingking. After understanding this position, so this research aims to reveal and understand this meaning in the policies of the Mangkunegaran kings. Based on the interaction analysis method of a qualitative approach with historical studies, this study collected informant insights and reference data through interviews, observation and document analysis. The results showed that the term konco wingking for Mangkunegaran kings was more appropriate with the term “garwo or sigaraning nyowo”, because the struggles and policies of the kings of Mangkunegaran involved women as a form of adaptive cultural system implementation, both in the domestic sphere and in formal education and even as a form cultural diplomacy. Keywords: Duchy of Mangkunegaran, king's policy, the role of women, cultural system